2019
DOI: 10.3389/fpls.2019.01047
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Corn Canopy Chlorophyll Content Using Derivative Spectra in the O2–A Absorption Band

Abstract: Chlorophyll (Chl) is one of the most important classes of light-absorbing pigments in photosynthesis, and the proportion of Chl in leaves is closely related to vegetation nutrient status. Remote sensing-based estimation of Chl content holds great potential for evaluating crop growth status in agricultural management, precision farming and ecosystem monitoring. Recent studies have shown that steady-state fluorescence contributed up to 2% on the apparent reflectance in the 750-nm spectral region of plant and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Signal noise for handheld spectroradiometers is highly susceptible to the sun's illumination, instrument quality, and environmental conditions [27]. To account for these issues, first-order and second-order derivative techniques have been widely applied to reduce signal noise by capturing subtle details in the spectral curve [28][29][30]. First-order and second-order derivatives are functions of mathematical change, where they represent the slope and curvature of the spectral curve, respectively [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Signal noise for handheld spectroradiometers is highly susceptible to the sun's illumination, instrument quality, and environmental conditions [27]. To account for these issues, first-order and second-order derivative techniques have been widely applied to reduce signal noise by capturing subtle details in the spectral curve [28][29][30]. First-order and second-order derivatives are functions of mathematical change, where they represent the slope and curvature of the spectral curve, respectively [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the tting models of the two relative variables, the results obtained by the three weighting methods all showed that the weighted rLAI-based models had higher accuracy than the weighted rCI red edge -based models. The optimal estimation models of potato yield can be determined as Equations (20) and (21). where yield (LAI) is the estimated yield using rLAI based on weighted growth stage.…”
Section: Estimation Of Potato Yield Based On Weighted Growth Stagementioning
confidence: 99%
“…Vegetation canopy spectrum is closely related to crop growth, especially the visible range affected by pigment and the near-infrared (NIR) bands affected by cell tissue and canopy structure [16][17]. Therefore, the vegetation index (VI) calculated by these bands has been widely used for the monitoring and estimation of vegetation characteristic parameters, such as leaf area index (LAI) [18], biomass [19], chlorophyll content [20], nitrogen content and carbon content [21], and achieved high accuracy. In addition, various VIs showed great differences when applied in diverse scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the fitting models of the two relative variables, the results obtained by the three weighting methods all showed that the weighted rLAI-based models had higher accuracy than the weighted rCIred edge-based models. The optimal estimation models of potato yield can be determined as Equations (20) and (21). As the final estimation models of potato yield were based on the relative yield model by adding the yield of the reference spot, their prediction ability remains unchanged (Table 3).…”
Section: Estimation Of Potato Yield Based On Weighted Growth Stagementioning
confidence: 99%
“…Vegetation canopy spectrum is closely related to crop growth, especially the visible range affected by pigment and the near-infrared (NIR) bands affected by cell tissue and canopy structure [16][17]. Therefore, the vegetation index (VI) calculated by these bands has been widely used for the monitoring and estimation of vegetation characteristic parameters, such as leaf area index (LAI) [18], biomass [19], chlorophyll content [20], nitrogen content and carbon content [21], and achieved high accuracy. In addition, various VIs showed great differences when applied in diverse scenarios.…”
Section: Introductionmentioning
confidence: 99%